Artificial Intelligence in Indo-Pacific - Putro, Yaries Mahardika; Tarigan, Muhammad Insan; Al Asyari, Haekal (University of Jember, 2023)
The use of Artificial Intelligence in the military is like two sides of a coin. It can provide convenience and aid in military operations but has the potential to hinder military operations. Dangerous and potentially catastrophic for humanity will be inevitable as no restrictions on its use. The United States, China, Australia, Japan, and India are examples of nations whose militaries have developed artificial intelligence technology. Geographically, Southeast Asia, which is located in the middle of these nations, will experience a significant impact due to its tight maritime borders if there is no international consensus on the military application of artificial intelligence technology. An autonomous or autonomous system to operate this technology will reduce the amount of human control and allow it to operate without any human intervention. It will be a threat to the application of the fundamental principles of international humanitarian law, such as the distinction principle, and proportionality principle. Where these principles are tightly intertwined with human command and control in making decisions regarding the execution of attacks. The article employs normative legal methodology. Furthermore, this paper endeavours to assess the pertinence of principles in international humanitarian law during the era of the artificial intelligence arms race. It also delves into the contribution of ASEAN in upholding stability, peace, and security in the Southeast Asia region, thereby reinforcing the importance of this research. This research emphasises the importance of aligning the progress of artificial intelligence in military contexts with core principles of international humanitarian law. It underscores the need for ASEAN to safeguard regional peace and security by establishing a novel regulatory framework that outlines restrictions on the development and deployment of artificial intelligence for military objectives.Keywords: Artificial Intelligence, International Law, Peace and Security, Southeast Asia.